Decision Support Systems Literature (2000–2026): A Scopus-Based Bibliometric Study of Research Patterns and Emerging Themes - Loso Judijanto (West Science Information System and Technology, 2026)
The current research tries to map and analyze the scientific field of the research in the topic of Decision Support Systems (DSS) from 2000 to 2026 with the help of bibliometric analysis with data collected in the Scopus database. Bibliometric analysis in this paper will be used to study co-authorship networks, citations networks, and keyword co-occurrences in order to understand research collaborations, influential literature in the field, and evolving themes of the scientific discussion. The analysis shows that the research in DSS has been increasing with each year and is characterized by inter-disciplinary nature, being closely related to information systems, computer science, and management disciplines. As for co-authors, the analysis showed the presence of clusters of co-authoring that includes leading researchers, institutions, and even countries, but there is still not much interaction between the clusters. Citations networks were dominated by theoretical articles that are related to healthcare and methods, however, in the last few years, there was a noticeable trend towards artificial intelligence-driven studies. Finally, analysis of keywords shows the development of theme clusters from clinical decision support systems to machine learning and other modern themes like sustainability. This study provides a comprehensive overview of the intellectual structure and development trajectory of DSS research, offering valuable insights for researchers and practitioners in identifying future research directions and opportunities for interdisciplinary collaboration.